Step-by-step explanation:
Here, the given expression is :
[tex]F(x) = 3x(x- 12x) + 3x^2-2(x-2)^2[/tex]
Now, let us first solve the given expression step wise:
[tex]F(x) = 3x(x-12x) +3x^2 -2(x-2)^2\\= 3x(-11x) +3x^2 -2(x^2 +4 -4x)\\= -33x^2 + 3x^2 -2x^2 -8+8x\\= -32x^2 +8x - 8\\\implies F(x) = -32x^2 +8x - 8[/tex]
Now, here the given statements are:
1. The term [tex]-2(x-2)^2[/tex] is simplified by first squaring the expression (x – 2).
TRUE
2. The simplified product is a binomial. TRUE
3. After multiplying, the like terms are combined by adding and subtracting.
TRUE
4. The parentheses are eliminated through multiplication. TRUE
5. The final simplified product is [tex]-28x^2 + 8x - 8[/tex] FALSE
As the simplified expression is: [tex](-32x^2 +8x -8)[/tex]